Klasifikasi Jenis Kismis Menggunakan Teknik Data Mining - Recha Abriana Anggraini; Ratningsih; Yanti Apriyani; Melisa Winda Pertiwi; Mira Kusmira; Saeful Bahri (Jurnal Kajian Ilmiah, 2024)
Raisins are one of the processed grape products that are often found in the market, raisins are one of the processed grape products by drying. The color and quality of raisins are usually determined by the type of grape and the drying process. To assess the quality of raisins, many methods can be used, one of which is the traditional method carried out by humans manually. However, since traditional methods are considered to tend to take a long time and errors often occur due to human error. Currently, machine vision systems can be used to assess the quality of raisins. In addition to assessing the quality of raisins, this method can also be used to identify and classify raisins. One way to classify raisins is to use data mining with classification algorithms. This research applies 5 data mining classification algorithms namely naïve bayes, decision tree, random forest, neural network and SVM. From the modeling results of the five algorithms, the neural network algorithm has the highest accuracy of 86.81%.